Identification Of Bivalves In Trikora Beach Waters, Teluk Bakau Village, Gunung Kijang District, Riau Islands Province - Rofian Isman; Eddiwan Eddiwan; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractTrikora beach is a coral beach in the village of Teluk Bakau. The beach is often found bivalva species. however at this time information has not been obtained about the types of bivalves in the area. This research will have been carried out in March 2019. Bivalve sampling is carried out at low tide three times in each sampling area with a time interval between sampling for one week. Samples of bivalves are taken by taking all the bivalves in the substrate base, roots and stems of seagrass by picking up by hand (hand collector). As for living bivalves, immersing themselves in the substrate is taken using a small shovel. Bivalve samples were then identified. The results showed that the bivalves obtained consisted of 4 Orders, 6 Families and 10 Species. The condition of water quality in Trikora Coast waters shows that the temperature is 30.1oC, brightness 538 cm, pH 8, dissolved oxygen 6.87 mg / L and salinity 32.1 mg / L.Keywords:Pantai Trikora, sampel bivalva, sampling area